INTERAKSI SOSIAL ORANG DENGAN HIV DENGAN LINGKUNGAN SOSIAL DI LEMBAGA SWADAYA MASYARAKAT WISMA KABUPATEN CIAMIS - Salma Fathia Nada; Teta Riasih (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2021)
Social interaction is one of the problems for people with HIV. Social interaction is useful for them to do their social functioning. The purpose of this research is to describe how people with HIV can do the social interaction in their social environment, with aspects of situations and actions within the family, neighbors, friends, and officers/officials of NGOs. The method is descriptive with quantitative approach. Sampling use the saturated sample. Data collection techniques were conducted using questionnaires, observations, and documentation studies to 40 people with HIV. Validity use the face validity. Reliability using Alpha Cronbach formula through SPSS calculations. Data analysis uses data processing, tabulation, and data interpretation. The results describe the overall social interactions of people with HIV, including high. Five aspects of social interaction are in the high category and three aspects are in the medium category. It shows that respondents already know to behave when doing social interaction.